Malaysian 10 Years Technology Expenditure - Noreen Balqis binti Muhammad; Irdhina Sofina Binti Shahrin; Nur Fara Syahadha Binti Anuar; Asmaa’ Aqilah Binti Mohd Rosli; Nurhanis Nabiha Binti Md Osman; Fuadah Johari (Universitas Islam Negeri Mataram, Indonesia, 2024)
Vol. 13 No. 2